2020
DOI: 10.2486/indhealth.2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of work-related events on depressive symptoms in Japanese employees: a web-based longitudinal study

Abstract: While a number of work-related events have been proposed as risk factors for depression, a majority of studies have focused only on a few events in a single study. Therefore, we conducted a web-based longitudinal study to comprehensively investigate the impact of various work-related events on depressive symptoms. Ten thousand Japanese workers representing the Japanese working population were recruited online and questioned on their experiences of 36 work-related events in the past year. Their depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Changes in overtime work may also have exerted a psychological effect on mental health. Since changes in the quantity and quality of work affect mental health status (Nishimura et al 2020), the observed increase in overtime work in groups B and C might severely impact the victim's mental health along with the cause of the extended working hours. Moreover, for white-collar workers, working on weekends has a one-and-a-half-to-two-fold increase in negative risks compared to those working overtime on weekdays in the case of mental ill-health (Sato et al 2020).…”
Section: Patterns Of Overtime Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in overtime work may also have exerted a psychological effect on mental health. Since changes in the quantity and quality of work affect mental health status (Nishimura et al 2020), the observed increase in overtime work in groups B and C might severely impact the victim's mental health along with the cause of the extended working hours. Moreover, for white-collar workers, working on weekends has a one-and-a-half-to-two-fold increase in negative risks compared to those working overtime on weekdays in the case of mental ill-health (Sato et al 2020).…”
Section: Patterns Of Overtime Workmentioning
confidence: 99%
“…While various types of work-related events such as disasters, interpersonal conflict in the workplace, and job characteristics (Tsuno et al 2018;Pennington et al 2018;Nishimura et al 2020;Gerhardt et al 2021) have been identified as risk factors for workers' mental health, the association between long working hours and workers' mental health is still contentious. During the IACI investigation for compensation determination, the existence and severity of 36 types of work-related events, including interpersonal conflict and overtime work, were evaluated as possible backgrounds for mental disorders (Nishimura et al 2020). However, earlier studies, including meta-analyses and systematic reviews, have reported inconsistent relationships between working overtime and mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal aggression in the workplace, such as workplace bullying, is one of many psychosocial job stress factors observed in the work environment [ 1 ]. Earlier studies, including our work based on the Japanese industrial accident compensation insurance records, have indicated that interpersonal conflict is a significant stressor in the workplace [ 2 , 3 ]. Customer and employee aggression can affect workers’ psychosocial environment, which may impair work performance and raise mental health issues [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, teleworking is believed to precede interpersonal conflict. A recent longitudinal study established a sequence of causality whereby interpersonal conflict at work resulted in depressive symptoms (Nishimura et al , 2020). Low interpersonal conflict at work has also been found to be associated with a psychologically caring climate.…”
Section: Introductionmentioning
confidence: 99%